Aboveground storage of hydrocarbon gas hydrates - Zotsenko, Mykola; Pedchenko, Larysa; Manhura, Andrii (My University, 2018)
The work objective is to substantiate the technical bases for the production of gas hydrate blocks directly on-site for further transportation and storage in above ground storages, as an alternative to transporting and storing gas in underground gas storages. The theoretical bases have been considered and processes of gas hydrate blocks producing, physical- mechanical characteristics of artificial hydrates with the purpose of determining the conditions of their storage and prolonged storage were tested in laboratory conditions. The construction of above ground gas hydrate storage in the form of a building, partially deepened in a ground, which is separated from the environment by a wall of gravel cement elements made by the mixing method were substantiated. It is proved that such a constructive solution for a long-term storage of gas hydrate blocks is the most economical in terms of energy consumption to maintain internal negative temperature.